The importance of healthy eating as a way to increase immunity through vitamins and minerals (Research, Society and Development, 2021)
Introduction: It is known that the immune system consists of a complex network of cells and molecules responsible for identifying an antigen and triggering an effector response through this stimulus, the responses are divided into two systems, innate immunity and adaptive to innate immunity presents a quick response to the body. General Objective: Identify the benefits of ingesting vitamins and minerals such as B6, B9, C, D, and Zinc, through food. Methodology: To carry out this study, we opted for a research in the modality of integrative literature review. The integrative review determines current knowledge on a specific topic, as it is conducted in order to identify, analyze and synthesize results of independent studies on the same subject. Results and Discussion: All nutrients, as well as vitamins and minerals are essential and each one of them plays a fundamental role for the body and should receive greater attention the supplementation of these nutrients are essential for the well-being and better functioning of the human body, contributing to the improvement of the quality of life. Final considerations: Through the development of this study, it can be shown that through nutrition, a better quality of life can be achieved, since it is proven that with the absorption of vitamins and minerals the human body has better development, and that is why it is very important that the people can adapt to new eating habits in order to avoid the emergence of deficiencies or even chronic pathologies caused by the lack of certain vitamins and minerals.